Growth-differentiation factor 15 as predictor of mortality in acute reperfused ST-elevation myocardial infarction: insights from cardiovascular magnetic resonance. Issue 8 (22nd February 2011) - Eitel, Ingo; Blase, Patrick; Adams, Volker; Hildebrand, Lysann; Desch, Steffen; Schuler, Gerhard; Thiele, Holger
Abstract : Objective: Growth-differentiation factor 15 (GDF-15), a stress-responsive member of the transforming growth factor beta cytokine superfamily, has emerged as a biomarker of increased mortality in cardiovascular disease. However, the exact pathophysiological mechanisms of GDF-15 in the cardiovascular system and in acute ST-elevation myocardial infarction (STEMI) are not well defined. The aim of this study was to determine the relation between GDF-15 and myocardial damage assessed by cardiovascular magnetic resonance (CMR) imaging and to evaluate the prognostic value of GDF-15 in a high-risk STEMI population exclusively reperfused by primary angioplasty. Design, setting, patients: GDF-15 concentrations were determined by an ELISA in 238 consecutive patients undergoing primary angioplasty in STEMI less than 12 h after symptom onset. Patients were categorised into two groups defined by the median GDF-15 value on admission. CMR was performed 3 days (IQR 2–4) after infarction for assessment of infarct size, myocardial salvage and microvascular obstruction. The primary clinical endpoint was mortality within 6 months after the index event. Results: Elevated GDF-15 concentrations over and above the median on admission were a strong predictor of mortality (19 vs one death, p<0.001) and major adverse cardiac events (27 vs nine events, p=0.001) at 6 months follow-up. Myocardial salvage was an inverse multivariable predictor of GDF-15 concentrations. Conclusions: GDF-15 on admission is a strong predictor of mortality in patients with STEMI reperfused by primary angioplasty, which is associated with decreased myocardial salvage and subsequent adverse clinical outcome. Clinical trail registration number: http://www.clinicaltrials.gov/ NCT00463749 .